A survey framework for setting an Augmented Reality (AR) roadmap in rolling stock organizations - Scheffer, Sara; Abbas Yawar (Cranfield University, 2024)
In anticipation of Industry 4.0’s significant impact on future maintenance systems, Augmented Reality (AR) emerges as a key technology. Even though AR has proven to be mature and applicable in maintenance practices, its practical implementation and challenges faced by organizations remain understudied. The integration of AR into organizational systems poses a crucial challenge, necessitating novel maintenance strategies, interdepartmental collaboration, and clearly defined goals. This research addresses the impact of AR on organizations, emphasizing the need for organizational readiness and adaption in maintenance processes, AR technology adoption, and IT infrastructure integration. This research demonstrates the development of an AR roadmap for rolling stock organizations through the application of a comprehensive survey framework. The study is based on a dual-pronged approach, incorporating a maturity and readiness assessment to ascertain the current state of AR adoption and organizational readiness. The survey framework systematically evaluates critical aspects such as existing technology infrastructure, operator skills, challenges faced, and desired organizational outcomes. The survey findings contribute to developing a tailored AR roadmap that addresses the specific needs and challenges of rolling stock maintenance operations. This research aims to enhance AR integration in rolling stock organizations and provides a practical guide for effective implementation.
Keywords: Augmented reality; rolling stock maintenance; roadmap; survey framework